Розвиток системи кадрового забезпечення готельного господарства України: методолого-методичні аспекти - Бунтова, Н.В. (Інститут демографії та соціальних досліджень НАН України, 2007)
В статье изложены особенности управления персоналом в гостиничном хозяйстве Украины в условиях трансформации рынка. Определены основные элементы системы кадрового обеспечения гостиничной отрасли. Разработаны основные направления кадровой политики по усовершенствованию системы кадрового обеспечения гостиничного хозяйства в современных условиях развития экономики. There are the features of staff control in Ukraine hotel facilities in conditions of the market trans formation in the article. The basic elements of a system of personnel maintenance of hotel branch are determined and the main directions of personnel policy on refinement of a system of personnel maintenance of hotel facilities in modern conditions of economy development are developed.